Fractionated human adipose tissue as a native biomaterial for the generation of a bone organ by endochondral ossification. (1st September 2018) - Guerrero, Julien; Pigeot, Sebastien; Müller, Judith; Schaefer, Dirk J; Martin, Ivan; Scherberich, Arnaud
Graphical abstract: Abstract: Many steps are required to generate bone through endochondral ossification with adipose mesenchymal stromal cells (ASC), from cell isolation to in vitro monolayer expansion, seeding into scaffolds, cartilaginous differentiation and in vivo remodeling. Moreover, monolayer expansion and passaging of ASC strongly decreases their differentiation potential. Here, we propose that adipose tissue itself can be used as scaffold for ASC expansion and endochondral ossification. Human liposuctions were fractionated and cultured for 3 weeks with proliferative medium in suspension. The resulting constructs, named Adiscaf, were compared to constructs generated with a previously developed, control approach, i.e. collagen sponges seeded with monolayer-expanded ASC. After 4 weeks of chondrogenic differentiation, Adiscaf contained cartilage tissue, characterized by glycosaminoglycans and collagen type II. After 2 additional weeks of hypertrophic differentiation, Adiscaf showed upregulation of hypertrophic markers at the gene expression and protein levels. After 8 weeks of in vivo implantation, Adiscaf resulted in ectopic bone tissue formation, including bone marrow elements. Adiscaf showed superior in vitro differentiation and in vivo performance as compared to the control paradigm involving isolation and monolayer expansion of ASC. This new paradigm exploits the physiological niche of adipose tissue and strongly suggests a higher functionality of cells inside adipose tissue after in vitro expansion. This study demonstrates that adult human adipose tissue used as a native construct can generate a bone organ by endochondral ossification. The concept could be exploited for the generation of osteogenic grafts for bone repair. Statement of Significance: In this study we used adult human adipose tissue as scaffolding materials (called Adiscaf) to generate a bone organ by endochondral ossification. Adiscaf concept is based on the culture of adipose tissue cells inside their native microenvironment for the generation of osteogenic grafts for bone repair. This simplified approach overcomes several limitations linked to the current techniques in bone tissue engineering, such as isolation of cells and inadequate properties of the biomaterials used as scaffolds. In addition, the present paradigm proposes to exploit physiological niches in order to better maintain the functionality of cells during their in vitro expansion. This project not only has a scientific impact by evaluating the impact of native physiological niches on the functionality and chondrogenic differentiation of mesenchymal progenitors but also a clinical impact to generate osteogenic grafts and/or osteoinductive materials for bone regeneration and repair.